PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOYJOY PT. AMERTA INDAH OTSUKA KOTA MEDAN - Ruth Felicia Angelika Pasaribu; Ira Lestari Sianipar; Yona Flora Siagian; Vier Sartika (JURNAL MANAJEMEN, 2019)
The purpose of the study was to examine and analyze the promotion and price on purchasing decisions at PT. Amerta Indah Outsuka Medan. The approach of this research is a quantitative research. The population in this study were some customers of PT. Amerta Indah Outsuka Medan who purchased at PT. Amerta Indah Outsuka Medan. The classic assumption test used includes: normality test, multicollinearity test, and heteroscedestity test. This data analysis model uses multiple regression analysis. The research concludes that partially and simultaneously promotion price have a significant effect on purchasing decisions at PT. Amerta Indah Outsuka Medan.